(untitled) (SNPRC Journal, 2024)
This study aims at investigating the applicability of socio-cultural resources in secondary-level classroom instructions and critically examines task-based approaches, methods, and techniques in fostering skill-based education within the selected study areas. Employing a qualitative research design, data were collected through classroom observations and semi-structured interviews. The analysis was conducted applying an interpretative paradigm. The findings indicate a rich presence of local knowledge and demonstrate its potential for integration into classroom instruction to promote task-based, practical learning. The study suggests that such locally grounded socio-cultural resources can be meaningfully incorporated into the secondary-level curriculum in Nepal to support the development of contextually relevant and skills-oriented education. Furthermore, it proposes strategic recommendations for integrating socio-cultural resources into instructional practices to enhance practical learning through functional, task-based pedagogy.